AB0017 Association study of genetic risk variants for psoriasis in a large cohort of psoriatic arthritis, psoriasis and controls of the spanish population and association with relevant clinical subphenotypes. (23rd January 2014) - Cañete, J.D.; Hernanz, J.M.; Fonseca, E.; Ferrandiz, C.; Unamuno, P.; Puig, L.; Fernandez-Sueiro, J.L.; Sanmartí, R.; Rodriguez, J.; Gratacόs, J.; Dauden, E.; Sánchez-Carazo, J.L.; et al.
Abstract : Background: Psoriatic Arthritis (PsA) is a complex disease with a substantial genetic risk component (first-degree relative risk ∼55). Recently, Genomewide Association Studies (GWAS) have expanded the number of risk loci for Psoriasis (Ps) in >20 new loci. Objectives: We have studied the association of Ps risk loci in PsA and purely cutaneous Ps (PsC). We have also analyzed the genetic association with several subphenotypes of clinical relevance. Methods: Loci showing the strongest statistical evidence of association to Ps were selected (n=32). The SNP having the highest statistical evidence was genotyped using Taqman technology in a cohort of n=955 PsA, 1, 050 PsC and 1, 497 hypernormal controls of the Spanish population. According to each subphenotype variable, the genetic association was performed using the chi-square test, logistic regression or linear regression. Results: We have replicated the association to COG6 and SERPINB8 loci with Ps for the first time in a Caucasian population. We have identified, for the first time, an association of PsA with variation at IFIH1, DPP6 and COG6 . Analyzing the association with other clinically relevant subphenotypes we have identified a strong association of LCE3D locus with the severity of cutaneous affection. We have also found a significant association of IL1RN gene with nail disease. Conclusions: Our findings show that common genetic variants associated to a complex phenotype like PsV influence PsA as well as different subphenotypes of high clinical relevance. Disclosure of Interest: None Declared